2004
DOI: 10.1590/s1415-47572004000300024
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of the effects of 2.5 and 10.5 GHz microwaves on human lymphocytes

Abstract: The biological effects of microwaves on living organisms remain highly controversial. Although some reports have suggested that microwaves may be directly or indirectly genotoxic, a direct action is unlikely because the low energy of microwave photons makes them unable to cause single-strand breaks in DNA. In this work, we examined the possible clastogenic properties of microwaves (2.5 and 10.5 GHz) on blood lymphocytes in vitro by monitoring the frequency of chromosomal aberrations. We also investigated wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
1
0
0
Order By: Relevance
“…The evaluation of chromosomal damage and its origin, assessed by indirect immunofluorescence CREST-MN analysis, showed no aneugenic or clastogenic effects for both types of signals. These observations are in agreement with other studies evaluating chromosomal damage by the conventional MN assay on different cellular types exposed to 2.45 GHz [ 71 , 72 ] or to other RF ranges [ 30 , 73 , 74 ]. Moreover, the absence of a clastogenic effect was confirmed by the γ-H2AX/53BP1 foci assay, which showed no significant induction of DSBs.…”
Section: Discussionsupporting
confidence: 93%
“…The evaluation of chromosomal damage and its origin, assessed by indirect immunofluorescence CREST-MN analysis, showed no aneugenic or clastogenic effects for both types of signals. These observations are in agreement with other studies evaluating chromosomal damage by the conventional MN assay on different cellular types exposed to 2.45 GHz [ 71 , 72 ] or to other RF ranges [ 30 , 73 , 74 ]. Moreover, the absence of a clastogenic effect was confirmed by the γ-H2AX/53BP1 foci assay, which showed no significant induction of DSBs.…”
Section: Discussionsupporting
confidence: 93%
“…An early study showed that RF exposure caused chromosomal aberration. [10], but most recent studies have shown no effect on chromosomal aberration [4], [11], [12]. Sister chromatid exchange has also not been detected in RF exposure [13], [14].…”
Section: B Chromosomal Aberration and Sister Chromatid Exchangementioning
confidence: 99%